2018
DOI: 10.1038/s41598-018-22550-z
|View full text |Cite
|
Sign up to set email alerts
|

Vector species-specific association between natural Wolbachia infections and avian malaria in black fly populations

Abstract: Artificial infection of mosquitoes with the endosymbiont bacteria Wolbachia can interfere with malaria parasite development. Therefore, the release of Wolbachia-infected mosquitoes has been proposed as a malaria control strategy. However, Wolbachia effects on vector competence are only partly understood, as indicated by inconsistent effects on malaria infection reported under laboratory conditions. Studies of naturally-occurring Wolbachia infections in wild vector populations could be useful to identify the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Indeed, pathogen inhibition may not be a consistent consequence of Wolbachia infection. For example, natural Wolbachia infections can increase the susceptibility of Aedes and Culex mosquitoes and Simulium blackflies to avian malaria parasites [ 40 42 ]. Therefore, it will be crucial to assess the impact of w Anga on malaria infections and vectorial capacity under natural, ecologically variable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pathogen inhibition may not be a consistent consequence of Wolbachia infection. For example, natural Wolbachia infections can increase the susceptibility of Aedes and Culex mosquitoes and Simulium blackflies to avian malaria parasites [ 40 42 ]. Therefore, it will be crucial to assess the impact of w Anga on malaria infections and vectorial capacity under natural, ecologically variable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Independently of hosts’ particular phylogenetic position and ecology, the same Wolbachia strain can have different effects on different genetic backgrounds within and across host species (Ranz et al ., 2003; Herbert and McGraw, 2018). A recent study in three black fly species in the genus Simulium found differential Wolbachia prevalence among species, suggesting host-specific interactions (Woodford et al ., 2018). However, the mechanisms behind these interactions are not clear.…”
Section: Discussionmentioning
confidence: 97%
“…In this small sample, Wolbachia was found not only to be the dominant symbiont but also to be represented by multiple sequence types. While Wolbachia is ubiquitous in arthropods from terrestrial environments, very few data on its distribution in aquatic species existed until recently, apart from analyses of holometabolous, medically important vectors with aquatic larval stages (principally mosquitoes [107], but also blackflies [108,109], and some limited surveys in aquatic crustaceans [110,111]). However, a 2017 meta-analysis of Wolbachia prevalence in aquatic insects (n = 228 species) estimated that >50% of species are infected, with Hemiptera exhibiting a particularly high prevalence (69%) [38].…”
Section: Discussionmentioning
confidence: 99%